Multilevel Effects of Community Capacity on Active Aging in Community-Dwelling Older Adults in South Korea - Junghee Kim; Hyeonkyeong Lee; Eunhee Cho; Kyung Hee Lee; Chang Gi Park; Byong-Hee Cho (Elsevier, 2020)
Purpose: This study aimed at identifying the level of active aging in older adults and the influence of the individual and community levels of community capacity on active aging. Methods: A cross-sectional survey was conducted on a stratified sample of 380 older adults living in 35 neighborhoods of five regions in Seoul, the capital of South Korea. The structured questionnaire included the Korean version of instruments that measure active aging and community capacity at the individual level. Secondary data including metropolitan statistical information, a public data portal, and a city plan were used to acquire community-capacity factors at the community level. Data were analyzed with multilevel models. Results: The overall active aging mean score was 3.00 ± 0.55 out of 5; the highest mean score was in the security domain (3.46 ± 0.65) and the lowest one was in the participation domain (2.71 ± 0.66). Individual factors associated with active aging included age, education, income, and community capacity at the individual level. At the community level, two community-capacity factors (senior leisure welfare facilities and cooperative unions) were significantly associated with active aging. In active aging, 6.4% and 4.1% of total variance could be explained by 35 neighborhoods, after considering individual and community level variables, respectively. Conclusion: This study showed that community capacity is important for active aging among older adults. Appropriate strategies that consider both individual and community factors, such as contextual indicators of community capacity, are necessary to improve active aging. Keywords: aging, community health nursing, multilevel analysis